Theorizing the immobility turn - Cairns, D.; Clemente, M. (The immobility turn: Mobility, migration and the covid-19 pandemic, 2023)
In this chapter, we recognize the importance of prior scholarship on the meaning of the multiplication of mobility, sometimes rebranded as ‘mobilities’ (Urry, 2007). We note the importance of expansionism during the pre-pandemic era, especially but not exclusively in regard to tourism. From a positive point of view, expansion meant the diversification of international mobility, opening up new possibilities for personal gratification in the leisure sphere and, more instrumentally, widening the potential field of opportunities for education, training and employment. This implies that the shift towards mobilities was not entirely superficial, especially when there were possibilities for life-enriching social and cultural exchange to take place, echoing ideas from research on lifestyle migration (see, for example, Benson and O’Reilly, 2009, 2016). Less publicized was the negative impact made by mobilities on the natural environment, and the disruption to social life that could take place within host communities where visitor numbers had expanded to unmanageable levels (see also Urry and Larsen, 2011).